Transcriptional Profiling Uncovers Human Hyalocytes as a Unique Innate Immune Cell Population - Boneva, Stefaniya Konstantinova; Wolf, Julian; Rosmus, Dennis-Dominik; Schlecht, Anja; Prinz, Gabriele; Laich, Yannik; Boeck, Myriam; Zhang, Peipei; Hilgendorf, Ingo; Stahl, Andreas; Reinhard, Thomas; Bainbridge, James; et al. (Frontiers in Immunology, 2020)
To decipher the transcriptional signature of macrophages of the human vitreous, also known as hyalocytes, and compare it to the profiles of other myeloid cell populations including human blood-derived monocytes, macrophages and brain microglia. This study involves a total of 13 patients of advanced age with disorders of the vitreoretinal interface undergoing vitrectomy at the University Eye Hospital Freiburg between 2018 and 2019. Vitreal hyalocytes were analyzed by fluorescence-activated cell sorting (FACS) and isolated as CD45+CD11b+CX3CR1+Mat-Mac+ cells using a FACS-based sorting protocol. RNA extraction, library preparation and RNA sequencing were performed and the sequencing data was analyzed using the Galaxy web platform. The transcriptome of human hyalocytes was compared to the transcriptional profile of human blood-derived monocytes, macrophages and brain microglia obtained from public databases. Protein validation for selected factors was performed by immunohistochemistry on paraffin sections from three human donor eyes. On average, 383 ± 233 hyalocytes were isolated per patient, resulting in 128 pg/µl ± 76 pg/µl total RNA per sample. RNA sequencing revealed that SPP1, FTL, CD74 and HLA-DRA are among the most abundantly expressed genes in hyalocytes, which was confirmed by immunofluorescence for CD74, FTL and HLA-DRA. Gene ontology (GO) enrichment analysis showed that biological processes such as “humoral immune response”, “leukocyte migration” and “antigen processing and presentation of peptide antigen” (adjusted p < 0.001) are dominating in vitreal hyalocytes. While the comparison of the gene expression profiles of hyalocytes and other myeloid cell populations showed an overall strong similarity (R2 > 0.637, p < 0.001), hyalocytes demonstrated significant differences with respect to common leukocyte-associated factors. In particular, transcripts involved in the immune privilege of the eye, such as POMC, CD46 and CD86, were significantly increased in hyalocytes compared to other myeloid cell subsets. Human hyalocytes represent a unique and distinct innate immune cell population specialized and adapted for the tissue-specific needs in the human vitreous. Vitreal hyalocytes are characterized by a strong expression of genes related to antigen processing and presentation as well as immune modulation. Thus, hyalocytes may represent an underestimated mediator in vitreoretinal disease and for the immune privilege of the eye.